1998
DOI: 10.1203/00006450-199805000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Maturational Change in the Cortical Response to Hypoperfusion Injury in the Fetal Sheep

Abstract: A characteristic of perinatal encephalopathies are the distinct patterns of neuronal and glial cell loss. Cerebral hypoperfusion is thought to be a major cause of these lesions. Gestational age is likely to influence outcome. This study compares the cortical electrophysiologic and histopathologic responses to hypoperfusion injury between preterm and near term fetuses. Chronically instrumented 0.65 (93-99-d, n = 9) and 0.9 (119-133-d, n = 6) gestation fetal sheep underwent 30 min of cerebral hypoperfusion injur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
1
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 41 publications
5
64
1
1
Order By: Relevance
“…The marked delay between initial inhibition of cerebral activity and mitochondrial function in contrast with the later final plateau of CytOx levels and the onset of cytotoxic edema is consistent with our previous reports showing that the rise in cerebral impedance is much slower during ischemia in preterm fetal sheep than at term (15,44). This suggests that actively regulated metabolism is effective in protecting the very immature brain for much longer than at term.…”
Section: Discussionsupporting
confidence: 81%
“…The marked delay between initial inhibition of cerebral activity and mitochondrial function in contrast with the later final plateau of CytOx levels and the onset of cytotoxic edema is consistent with our previous reports showing that the rise in cerebral impedance is much slower during ischemia in preterm fetal sheep than at term (15,44). This suggests that actively regulated metabolism is effective in protecting the very immature brain for much longer than at term.…”
Section: Discussionsupporting
confidence: 81%
“…Chronic instrumentation also allows a wide range of practical and clinically pertinent cerebral insults to be administered. These include global cephalic ischemia [65], systemic hypotension or hypoxemia [66][67][68], single or repeated cord occlusion [69][70][71], increased intracranial pressure [72], and administration of infectious agents or exogenous inflammatory mediators [73][74][75]. These insults can be graded in intensity and duration to mimic the human situation.…”
Section: Advantages and Disadvantages Of The Fetal Sheep To Model Wmimentioning
confidence: 99%
“…These experimental studies support that a complex interplay of factors related to cerebrovascular immaturity predispose preterm cerebral white matter to injury from hypoxia-ischemia. Studies of global cerebral hypoperfusion found that the mid-gestation animal displayed a predilection to subcortical WMI, whereas the near term animal displayed predominantly parasagittal cortical neuronal injury [65,87]. A variable degree of WMI was also detected after systemic hypotension arising from intermittent or partial umblical cord occlusion [88,89].…”
Section: Hypoxia-ischemia In Fetal Sheep Generates Pathological Featumentioning
confidence: 99%
See 2 more Smart Citations